DEVELOPMENT OF EXPRESSIVE SPEECH FUTURE TUTORS: METHODICAL ASPECT - Rudenko Yulia А. (Educological discourse, 2015)
The article deals with the development of expressive speech of the future tutors of preschool educational institutions in the light of the conceptual provisions of the cultural approach. The author proved the usefulness of clarity in the process of professional - voice training of future teachers, described the essence of the methodological aspects of technology development expression of speech.